GREEN ACCOUNTING DAN FAKTOR YANG MEMPENGARUHINYA - Kurniawan, Elan (Kinerja, 2023)
This study aims to determine the capital structure and corporate value of green accounting disclosures. The sample used in this study is a company listed on the Indonesia Stock Exchange by issuing annual financial reports for the 2020 – 2022 period, samples taken by 12 companies. The independent variable of this research is capital structure which is measured by Debt to Equity Ratio while company value is measured by price to book value. The dependent variable of this research is disclosure of green accounting which is measured by the Global Reporting Initiative (GRI) index value. The results show that capital structure has no significant effect on green accounting disclosures and firm value has a significant effect on green accounting disclosures.